The Group Supportive Therapy Model and Disaster Preparedness Training in Improving the Preparedness of School Community Toward Disaster in West Sumatera - Renidayati; Zolla Amely Ilda; Reflita (POLTEKKES KEMENKES PADANG, 2023)
West Sumatra gets the fifthranks in the top disaster-prone province in Indonesia. The level of disaster preparedness in the school environment is at the lowest position compared to the preparedness in the community. This study aimed to implement the Model Group Supportive Therapy and Disaster PreparednessTraining to improve the school community's preparedness for disasters in West Sumatra. The research design used